PENGARUH SISTEM SAMSAT CORNER TERHADAP PENINGKATAN PELAYANAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR (Studi Pada SAMSAT Corner Mall Sri ratu Kediri) - Ndae, Gabriel Febri (Jurnal Mahasiswa Perpajakan, 2015)
SAMSAT Public Office has done some innovations in order to support public services one of which is by opening SAMSAT Corner in the shopping centre such as mall and hypermart. SAMSAT CornerÂ  provides an easier, faster, and more comfortable way for the people in paying vehicles tax. By submitting STNK (Surat Tanda Nomor Kendaraan), BPKB (Bukti Kepemilikan Kendaraan Bermotor) and KTP (Kartu Tanda Penduduk), the taxpayers will be able to do the payment and and KTP (Kartu Tanda Penduduk), the taxpayers will be able to do the payment and validation of STNK (Surat Tanda Nomor Kendaraan) only within Â± 5 minutes. This research design is explanatory research with quantitative approach. The samples used are 100 respondents of the customers of SAMSAT Corner in Sri Ratu Mall Kediri . Keywords : Tax access, Facilities, Complain Center, Website, The improvement of vehicles tax payment service